Expression and clinical significance of IL-8 and Wnt2 in Helicobacter pylori-infected gastric cancer patients - Lin, Li; Tao, Ruiyu; Cai, Yonggang; Zhao, Qiang; Yang, Ke; Yang, Wenjuan; Guo, Fengxia (The Journal of Infection in Developing Countries, 2024)
Introduction: We assessed the expression levels of interleukin-8 (IL-8) and Wnt2 in Helicobacter pylori-infected gastric cancer (GC) patients, and investigated the association of these proteins with prognosis. Methodology: Seventy-two GC patients, including 40 cases with H. pylori infection and 32 cases without H. pylori infection, were enrolled. Tumor and para-tumor normal tissues were collected. H. pylori infection was determined using the rapid urease test and Warthin-Starry silver staining. The expressions of IL-8 and Wnt2 were assessed using immunohistochemistry. The association between H. pylori infection, IL-8, Wnt2, and pathological and clinical data was analyzed. The relationship between H. pylori, IL-8, Wnt2, and prognosis was assessed using survival curves and regression analyses. Results: The expression levels of IL-8 and Wnt2 in GC tissue significantly exceeded that in normal mucosa. The expression levels of IL-8 and Wnt2 were significantly higher in patients with H. pylori infection, than in those without H. pylori infection; and a positive correlation was observed between IL-8 and Wnt2 expressions. The positivity rate of IL-8 and Wnt2 in early-stage GC without lymph node metastasis markedly differed from that in advanced-stage GC with lymph node metastasis. Additionally, the survival rate of GC patients with positive IL-8 and Wnt2 expressions was significantly lower than in patients without such expression patterns. Clinical stage and Wnt2 were identified as independent prognostic factors of GC. Conclusions: IL-8 and Wnt2 were prognostic indicators for GC. H. pylori and IL-8 were not independent prognostic factors, whereas Wnt2 could independently serve as a prognostic factor for GC.